2017
DOI: 10.1111/jbg.12280
|View full text |Cite
|
Sign up to set email alerts
|

A genetic analysis of meat compositions in Japanese Black cattle: Genetic parameters and sex influence

Abstract: Meat composition in beef is related to eating quality and food functionality. Genetic parameters for several meat compositions including free amino acid, peptide and sugar, however, remain poorly described. In this study, we estimated genetic parameters for 51 meat components, including free amino acids, peptides, sugars and fatty acid compositions, and two carcase traits in 1,354 heifers and 1,797 steers of Japanese Black cattle. Heritability estimates were generally equivalent to or moderately greater than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 29 publications
5
9
1
Order By: Relevance
“…High additive heritability estimates were found in glycogen (0.516), C18:1 (0.642), and MUFA (0.644). There have only been a few reports of heritability estimates for glycogen, and the estimates vary widely depending on the report [0.34 by Komatsu et al (2014) and 0.607 by Onogi et al (2017)]. The heritability of 0.516 for glycogen in the current study was within a range of the estimates of the previous studies.…”
Section: Ta B L Esupporting
confidence: 62%
See 2 more Smart Citations
“…High additive heritability estimates were found in glycogen (0.516), C18:1 (0.642), and MUFA (0.644). There have only been a few reports of heritability estimates for glycogen, and the estimates vary widely depending on the report [0.34 by Komatsu et al (2014) and 0.607 by Onogi et al (2017)]. The heritability of 0.516 for glycogen in the current study was within a range of the estimates of the previous studies.…”
Section: Ta B L Esupporting
confidence: 62%
“…In fatty acid traits, the means of C18:1 and MUFA were 52.0% and 57.9%, respectively. Many measurements of fatty acid composition have been reported in Japanese Black cattle, and the C18:1 and MUFA content range from 49.0% to 60.1% and 57.1% to 63.7%, respectively (Inoue et al., 2008, 2011, 2017; Nogi et al., 2011; Onogi et al., 2017; Sakuma et al., 2017; Suzuki et al., 2017), although fatty acid composition changes depending on the feed, and the fatty acids and muscles sampled. The measurements of C18:1 and MUFA in this study were within the range of the measurements in previous studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Onogi et al. () reported the moderate heritability estimates for taurine and β‐alanine (0.48 and 0.35, respectively) in trapezius muscles of 3,070 Japanese Black cattle. For β‐alanine, the heritability estimate in this population was low, but two significant regions (proportion = 0.05) were detected on chromosomes 22 and 29.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Onogi et al. () reported that heritability estimates for free amino acids and peptides in Japanese Black cattle were equivalent to or moderately greater than those found by Mateescu et al. () and Sakuma et al.…”
Section: Introductionmentioning
confidence: 86%